2007
DOI: 10.1007/s11211-007-0036-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Fairness Matter More to Some than to Others? The Moderating Role of Workplace Status on The Relationship Between Procedural Fairness Perceptions and Job Satisfaction

Abstract: Three field studies explored the relations among status, procedural fairness, and job satisfaction in the workplace. Study 1 revealed that status differences moderated the relationship between procedural fairness and job satisfaction such that there was a stronger relationship between procedural fairness and job satisfaction for individuals with higher perceived status than for those with lower perceived status. Study 2 examined a possible underlying psychological mechanism for the moderating effect of perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…In a follow-up study, Sunshine and Heuer (2002) showed that when people interact with other members of their ingroup, the effect of respect on their fairness judgments is mediated by their perception that they deserve respect because of their within-group status (e.g., higher status as greater deservingness). A similar finding was recently reported by Diekmann et al (2007).…”
Section: Contextual Moderationsupporting
confidence: 92%
See 1 more Smart Citation
“…In a follow-up study, Sunshine and Heuer (2002) showed that when people interact with other members of their ingroup, the effect of respect on their fairness judgments is mediated by their perception that they deserve respect because of their within-group status (e.g., higher status as greater deservingness). A similar finding was recently reported by Diekmann et al (2007).…”
Section: Contextual Moderationsupporting
confidence: 92%
“…The first pertains to the role of deservingness assessments on procedural justice. Numerous theorists have argued that notions of deservingness are central to both distributive (Crosby, 1982;Lerner, 1965Lerner, , 1977Major, 1994;Major, McFarlin, & Gagnon, 1984) and procedural justice (Diekmann, Sondak, & Barsness, 2007;Heuer et al, 1999;Sunshine & Heuer, 2002). For example, Heuer et al (1999) argued that judgments of procedural justice are influenced by assessments of whether treatment received in a social encounter is in accord with the treatment deserved, and their research showed that people with high self-esteem feel more deserving of respectful treatment than people with low self-esteem.…”
Section: Contextual Moderationmentioning
confidence: 99%
“…Additional research by Van Prooijen, Van den Bos, and Wilke (2002) and by Diekmann, Sondak, and Barsness (2007) has suggested a more nuanced relation between procedural fairness and status. Van Prooijen et al hypothesized that, when status is accessible in members' minds, procedural fairness will have a stronger psychological impact.…”
Section: Statusmentioning
confidence: 99%
“…Additional research by Van Prooijen, Van den Bos, and Wilke (2002) and by Diekmann, Sondak, and Barsness (2007) has suggested a more nuanced relation between procedural fairness and status. Van Prooijen et al.…”
Section: Implications Of Procedural Fairness For the Collective Selfmentioning
confidence: 99%
“…Those perceptions of fairness held by organizational members towards those three dimensions and the integration of the dimensions formed the foundation for the organizational justice construct (Greenberg 1987(Greenberg , 1990Greenberg and Cropanzano 2001;Greenberg et al 1985). Since organizational justice and its dimensions have repeatedly been directly linked to performance, commitment, citizenship behavior, and job satisfaction (Begley et al 2006;Cohen-Charash and Spector 2001;Colquitt et al 2001;Colquitt et al 2002;Diekmann et al 2007;Fields et al 2000;Folger and Konovsky 1989;Jordan et al 2007a;Lam et al 2002;Sweeney and McFarlin 1997) further study within high school athletic departments was warranted.…”
Section: Organizational Justicementioning
confidence: 99%